Don't Make Me Angry: Frustration-Induced Anger and Its Link to Aggression in Women With Borderline Personality Disorder - Bertsch, Katja; Back, Sarah; Flechsenhar, Aleya; Neukel, Corinne; Krauch, Marlene; Spieß, Karen; Panizza, Angelika; Herpertz, Sabine C. (Frontiers in Psychiatry, 2021)
Aggression is a prominent interpersonal dysfunction of individuals with borderline personality disorder (BPD). Being predominantly reactive in nature, aggression in BPD is often triggered by frustration, provocation, or social threat and is associated with intense anger and an inability to regulate this strong, negative emotion. Building on previous research, we were interested in investigating negative emotionality in general and anger in particular in women with BPD before and after frustration induction. To achieve this, 60 medication-free women with BPD and 32 healthy women rated the intensity of negative emotions (angry, frustrated, upset, embarrassed, nervous) before and after performing a Titrated Mirror Tracing Task, which reliably induces frustration and distress. As expected, women with BPD reported significantly greater intensity of negative emotions before and after frustration than healthy women. Specifically, they showed a significantly stronger frustration-induced increase in anger, while other negative emotions remained unaffected by frustration induction. This anger increase was significantly related to aggressive behavior reported in the two weeks prior to the experiment, as well as to the level of frustration experienced in the experiment itself, but not with emotion dysregulation. The current data confirm the important role of frustration-induced anger independent of emotion dysregulation in BPD, in particular with regard to aggression, a prominent interpersonal dysfunction of this disorder. These findings underline the importance of interventions with particular focus on anger.